Confucian Ethics and the Juvenile Justice System in the Thai Institutional Context - Chitov, Alexandre Nikolaevich (ASEAN Journal of Legal Studies, 2018)
Providing education for juvenile offenders is one of the basic policies in the Thai criminal justice system. One of the weak sides of this policy is a lack of effective moral education. Confucianism is not simply a religion. It possesses a wealth of moral ideas that can be utilized in the rehabilitation of Thai youth that committed crime. This paper presents some comparison of Confucianism with Buddhist as well as Christian ideas. In its emphasis on the duty towards family, the state and the humankind, the Confucian ethics is unique and differs not only from the Buddhist moral teaching, which is concerned with the individual salvation from suffering, but also from Christian ethics which deals mostly with the relationship of a human being with his or her Creator. Confucian ethics is different. It is not concerned much with the transcendental God in a Christian meaning, or the personal salvation from suffering in a Buddhist meaning, rather it deals mostly with educating people to perform their daily duties faithfully and in the right manner. This paper outlines the basic features and methods of Confucian ethics when applied to juvenile justice system.